Acute Acalculous Cholecystitis Induced by Acute Hepatitis B Virus Infection - Riyadh Ali Mohammed; Wisam Ghadban; Osama Mohammed (Case Reports in Hepatology)
During the course of acute viral hepatitis, some functional and anatomical changes to the gallbladder can occur. Acute acalculous cholecystitis (ACC) is a rare complication of acute hepatitis B virus infection; only few cases are reported as ACC associated with acute hepatitis B virus infection. ACC cases are self-limiting, while other limited cases can progress to a gangrenous state, perforation, and even death. We present a 27-year-old female case diagnosed to have acute acalculous cholecystitis and associated with acute hepatitis B virus infection, and she recovered within one week of her presentation without complication or surgical intervention.